ANALISIS STRATEGI PEMASARAN BERBASIS MEDIA SOSIAL DALAM MENINGKATKAN LOYALITAS PELANGGAN - Andini Rahayu Putri; Aurick Mathias Danarya; Febry Tarigan; Ondo Apostel; Hasyim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes social media–based marketing strategies in enhancing customer loyalty in the digital era. The problem addressed in this research is the increasing competition among businesses and the challenge of maintaining customer loyalty amid rapidly evolving digital platforms. The objective of this study is to examine how the use of social media marketing strategies, including content creation, customer engagement, and online promotion, can influence customer loyalty. This research employs a qualitative descriptive method through literature review and case study analysis of businesses that actively utilize social media as a marketing tool. The findings indicate that social media marketing plays a significant role in building strong relationships between businesses and customers by enabling interactive communication, personalized content, and continuous engagement. Furthermore, effective use of social media platforms contributes to increased customer satisfaction, trust, and long-term loyalty. Therefore, businesses are encouraged to optimize their social media strategies to remain competitive and sustain customer retention in a dynamic market environment.